Implementasi Meditasi Vipassanā Bhāvanā dalam Pembinaan Spiritualitas Umat Buddha di Abhisamaya Forest Monastery - Veni Veni; Marjianto Marjianto; Walyono Walyono (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Vipassanā bhāvanā is one of the essential meditation practices in Theravāda Buddhism that aims to develop mindfulness, self-awareness, and wisdom by observing bodily and mental experiences directly. While many previous studies have focused on the psychological benefits of meditation, this study emphasizes the technical practice of vipassanā bhāvanā within a forest monastery setting. This research aims to describe how vipassanā bhāvanā meditation is implemented in fostering Buddhist spirituality at Abhisamaya Forest Monastery, Bukit Rebo, Sungailiat Bangka. This study used a descriptive qualitative approach with a case study design. Data were obtained through in-depth interviews with two Buddhist monk meditation guides and nine meditation participants, non-participant observation during retreat activities, and documentation of institutional and field activities. The results show that vipassanā bhāvanā is practiced through a structured process involving mindfulness of breathing, sitting meditation, walking meditation, mental noting, noble silence, Dhamma talks, and meditation interviews. The implementation of this practice is supported by a conducive forest environment, the guidance of meditation teachers, disciplined schedules, and adequate facilities. Participants also experienced several obstacles, including bodily pain, drowsiness, wandering thoughts, mosquitoes, weather conditions, and uneven walking paths. The findings indicate that structured vipassanā practice in a forest monastery can support Buddhist spiritual development by strengthening self-awareness, inner calm, emotional regulation, and positive attitudes in daily life.